Egg white based biological microlasers. (5th August 2020) - Nguyen, Toan Van; Mai, Hanh Hong; Nguyen, Thuong Van; Duong, Dung Chi; Ta, Van Duong
Abstract: Biolasers made of biological materials hold great potential for implantable biosensing and cell-tracking. However, the current bio-extracted materials used for biolasers generally require a complicated synthesis process and therefore suffer from high cost. In this work, we demonstrate that low-cost natural egg white is an excellent biomaterial for a laser cavity. Using a simple dehydration method, dye-doped goose egg white microspheres are obtained with various sizes from 20 to 160 µ m in diameter. These microspheres can act as excellent laser sources under optical excitation with lasing threshold of ∼26 µ J mm −2 and quality (Q) factor up to 3 × 10 3 . The lasing mechanism is studied and ascribed to the whispering gallery mode. Size-dependence of the lasing spectrum and Q factor are also investigated. Owing to the ease of fabrication, the cost-effectiveness, goose egg white based microlasers are promising for biosensing and bioimaging applications.